THE ROLE OF SELECTED HIGHER EDUCATIONAL INSTITUTIONS (HEIS) AND LOCAL GOVERNMENT UNITS ON INTEGRATING FOOD HERITAGE RESEARCH INTO POLITICAL PRIORITIES: A PUBLIC POLICY ANALYSIS OF LUZON ISLAND, PHILIPPINES - Avi Ben Pestanas Andalecio (School of Tourism, Universitas Ciputra Surabaya, 2021)
The purpose of this study is to show how food heritage, specifically Filipino Pancit, define the culture oftheir citizens, investigate the efforts of Local Government Units (LGUs), and examine the role of a selectedHigher Educational Institution (HEI) as a partner of LGUs in safeguarding food heritage. The researcher used frameworks from international and national cultural agencies and researchers. Observation and in-depth interviews were also used for the documentation process through case study technique, which examined the aspects of statutory control and safeguarding mechanisms to determine the political prioritiesof involved LGUs and the selected HEI’s role in safeguarding food heritage in the islands of Luzon,Philippines. Findings suggest that LGUs’ sheer political will, knowledge, and awareness on issues onheritage conservation, openness, sustainable practices, and multi-stakeholder participation are essential inrobust protection vis-à-vis culture and heritage conservation. This comes with the active participation ofstakeholders, especially academic institutions, which provide expertise and extra leg work on researchbacked by their advocacy rooted on Filipino identity and sustainability to support policies of the government.Ultimately, research-based policymaking is key to open opportunities not just on intangible cultural heritagelike Filipino Pancit but on culture and heritage conservation in general.